Layanan Konseling Kelompok Berbasis Permainan dalam Pembentukan Sikap Toleransi - Mustaqim Pabbajah; Murtiningsih Murtiningsih; Nararya Rahadyan Budiono (Indonesian Journal of Teaching and Teacher Education, 2022)
Games as learning media have not received a portion of attention in the world of education. This paper aims to explain that through game-based group services can foster an attitude of tolerance. The study is based on a qualitative research type with data sources in the form of observation and literature studies. The study findings show that playing Uno is considered capable of forming an attitude of tolerance through group counseling services. The UNO game with a group counseling service approach is considered capable of forming an attitude of tolerance. This can be seen from the UNO game process which contains the value of togetherness and respect for differences. In group counseling, the UNO card simulation game technique is an alternative to foster tolerance in diversity. The UNO card simulation game by forming a circle can increase intimacy, unity and kinship between members. The discussion process that is built in this technique is considered to be able to train individuals to control themselves, respect and respect various differences of opinion. Thus, playing UNO in groups can form an attitude of togetherness and tolerance for cultural, religious and ethnic differences. This study suggests the need to use games in building an attitude of tolerance, especially in the process of multicultural learning in educational institutions.